Kinetics and Adsorption Equilibrium of Methylene Blue Using Shell and Coconut Husk Ash from Waste of Tofu Industry Cooking Process Activated with Sulfuric Acid - Yulianti, Eny; Falahiyah, Falahiyah; Fahmi, Fariz Rifqi Zul; Istighfarini, Vina Nurul; Aini, Nur (Department of Chemistry, Faculty of Science and Technology UIN Maulana Malik Ibrahim Malan, 2025)
Methylene blue adsorption was conducted using ash from coconut husks and shells, derived from industrial tofu fuel waste in Malang City. The ash was activated using 2% H₂SO₄. The determination of the optimum adsorption conditions for methylene blue included variations in contact time, solution pH, and adsorbent dosage. This study also examined adsorption capacity and adsorption isotherms. The ash was characterized using XRD to identify the silica phase present in the ash. The results showed that the optimum conditions for adsorbing 50 mL of methylene blue at a concentration of 13.97 mg/L were a contact time of 75 minutes, a pH of 3, and an adsorbent dosage of 0.5 grams. The adsorption capacity of methylene blue was found to be 4.533 mg/g, and the adsorption isotherm of methylene blue using H₂SO₄-activated coconut husk and shell ash followed the Freundlich isotherm model more closely than the Langmuir isotherm. XRD analysis indicated that the crystallinity and purity of silica in the ash activated with 2% H₂SO₄ improved due to the removal of impurity peaks from KCl and HNaCO₃